The relationship between college students' belief in a just world and internet addiction: the moderating effect of legal cognition - Jianhua, He; Haoliang, Zhu; Kanze, Li; Shuhui, Xu (Frontiers in Psychology, 2025)
BackgroundPrevious studies have explored various personality and emotional variables influencing internet addiction. However, few have examined the impact mechanism of legal cognition on internet addiction. This study examined the relationship between belief in a just world and internet addiction, investigating whether legal cognition could moderate the effect of belief in a just world on internet addiction.MethodsThe study used the Belief in a Just World Scale, the Internet Addiction Scale, and the Legal Cognition Assessment Scale to survey 532 college students from universities in mainland China.ResultsCorrelation analysis indicated a significant negative correlation between belief in a just world and internet addiction; belief in a just world negatively predicted internet addiction, and both the overall score of legal cognition and abstract legal cognition moderated this relationship.ConclusionsCollege students' internet addiction was influenced by belief in a just world and legal cognition, suggesting that interventions for internet addiction among college students could involve cognitive-behavioral therapy and education on the rule of law.